Germination of grass species from dry and wet grasslands in response to osmotic stress under present and future temperatures. Issue 12 (7th December 2022) - Souza, Cristiele S.; Ramos, Desirée M.; Barbosa, Eduardo R. M.; Borghetti, Fabian
Abstract: Premise: Seed germination is controlled by the soil microclimate, which is expected to change with the temperature increase and rainfall irregularity predicted for the future. Because changes in soil characteristics directly affect species recruitment, vegetation dynamics and resilience, we investigated how caryopses of native grasses from dry and wet grasslands respond to water stress under current and future temperature regimes. Methods: Caryopses were collected from 10 grass species in dry and wet grasslands, subjected or not to a fire event, and tested for germination at increasing osmotic potential (0 to –1.0 MPa) at current (17°/27°C night/day) and future (23°/33°C) simulated temperatures. Results: The viability and germination percentages of caryopses from both dry and wet grassland species were progressively reduced as osmotic stress increased, irrespective of temperature regime. The viability of caryopses from wet grassland species was reduced under the future temperature regime, irrespective of osmotic potential. The slow germination of caryopses of dry grassland species at the present temperature regime was absent when they were incubated in the future temperature regime. Conclusions: More intense water stress reduced the survival of caryopses for both dry and wet grassland grass species. The predicted future temperature regime reduced the viability of wet grassland species and altered the germination strategy of dry grassland species. These results indicate that increasing water stress and temperature predicted for the future may compromise the recruitment potential of dry and wet grassland species and directly impact the dynamics and resilience of these ecosystems.